GW24-e3036 Association between paraoxonase activity and coronary heart disease with normal serum lipid levels. (1st October 2013) - Fan, Wang; Bai, Tao; Hui Chen, Xiao; Zheng, Yang
Abstract : Objectives: To investigate association between the reaction system of paraoxonase (PON), biomarkers of oxidative stress, and coronary heart disease (CHD) with normal serum lipid levels. Methods: A total of 60 randomised Han Chinese subjects (32 men and 28 women) in Northeast China, consisting of 31 case subjects (17 men and 14. women, aged 61.20. ± 1.34 years) with CHD but expect myocardial infarction and 29 control subjects (15 men and 14 women, aged 59.70 ± 2.85 years) without coronary artery disease and susceptible factors in atherosclerosis-related diseases, were enrolled in this case-control study, which was performed in the Cardiovascular Center, the First Hospital of Jilin University, Changchun. Patients were diagnosed by coronary angiography. We measured biomarkers of oxidative stress, such as PON activity, HNE-LDL, MDA-LDL, Concentration of protein carbonyls, GSH, T-AOC, H2 O2, and anti-hydroxyl radical antioxidant capacity. Statistical analysis was performed using the nonparametric Kruskal-Wallis test for comparison of vessel disease and biomarkers of oxidative stress. Moreover, we analysed the correlations between PON activity and levels of other biomarkers of oxidative stress by Spearman's correlation. Meanwhile, we plotted 3-dimensional (3D) figures (independent variables, PON activity and Ca 2+ ; dependent variables, levels of other biomarkers of oxidative stress), and analysed the relation between them by response surface regression (RSR). Results: H2 O2 (4.40 ± 1.62 uM), systolic pressure (188.80 ± 21.87 mmHg), hypersensitive c-reactive protein (3.90 ± 3.13 mg/l )in the group of coronary heart disease with normal serum lipids are significantly higher than control group H2 O2 (3.70 ± 1.94 uM), systolic pressure (176.70 ± 34.07 mmHg), hypersensitive c-reactive protein (2.10 ± 2.24 mg/l) (both were P<0.05 ). Comparing the group of coronary heart disease with normal serum lipids with control group, the difference of HNE-LDL, MDA-LDL, carbonyl protein concentration, GSH, T-AOC, anti-hydroxyl radical antioxidant capacity, diastolic pressure, serum ions (K +, Na +, CL -, Ca 2+ ) and serum lipids (TG, TC, HDL-c, LDL-c)level have no statistical significance (both were P>0.05 ). Comparing organophosphatase activity of PON in the group of coronary heart disease with normal serum lipids (96.00 ± 36.72 U/ml) with control group (89.90 ± 16.27 U/ml), there is no statistically significant difference ( P>0.05 ) . HNE-LDL levels is not significantly associated with levels of serum lipids ( P > 0.05 ). RSR revealed that the reaction system of PON activity and Ca 2+ significantly contributed to the levels of LDL-HNE ( P < 0.05 ). However, the interaction of Ca 2+ significantly contributed to the CHD with normal serum lipid levels ( P < 0.05 ). Conclusions: H2 O2, systolic pressure, hypersensitive c-reactive protein contributed to the CHD with normal serum lipid levels. The reaction system of PON activity and Ca 2+ contributed to the levels of LDL-HNE. However, the interaction of Ca 2+ contributed to the CHD with normal serum lipid levels.